Production of a Monoclonal Antibody Targeting the M Protein of MERS-CoV for Detection of MERS-CoV Using a Synthetic Peptide Epitope Formulated with a CpG–DNA–Liposome Complex - Park, Byoung Kwon (Int J Pept Res Ther, 2018)
The Middle East respiratory syndrome-related coronavirus (MERS-CoV) contains four major structural proteins, the spike glycoprotein, nucleocapsid phosphoprotein, membrane (M) glycoprotein and small envelope glycoprotein. The M protein of MERS-CoV has a role in the morphogenesis or assembly of the virus and inhibits type I interferon expression in infected cells. Here, we produced a monoclonal antibody specific against the M protein of MERS-CoV by injecting BALB/c mice with a complex containing the epitope peptide and CpG–DNA encapsulated with a phosphatidyl-β-oleoyl-γ-palmitoyl ethanolamine (DOPE):cholesterol hemisuccinate (CHEMS). The monoclonal antibody was reactive to the epitope peptide of the M protein of MERS-CoV which was confirmed by western blotting and immunoprecipitations. Indirect immunofluorescence assay and confocal image analysis showed that the monoclonal antibody binds specifically to the M protein of MERS-CoV in the virus-infected cells. Further studies using this monoclonal antibody may provide important information on the function of the M protein and its future application in diagnostics.